Efficiency of Commonly Used Disinfectants and Antiseptics against Pathogenic Bacteria Isolated from Tripoli University Hospital, Libya - Mahmoud Ashawesh; Sara Alashhab; Sakena Kori (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives: Disinfectants and antiseptics are widely used in hospitals and other healthcare centers to ensure the prevention of nosocomial infections and provide efficient infection control. Numerous studies have recently shown that hospital-acquired bacteria are developing resistance against such compounds. The purpose of this study is to examine the effectiveness of the commonly used disinfectants and antiseptics against a group of nosocomial bacteria isolated from Tripoli University Hospital, Libya. Material and Methods: Five bacterial pathogens isolated from different hospital departments are klebsiella spp., Proteus spp., Escherichia coli (E. coli), Acinetobacter spp., Staphylococcus aureus (S. aureus). These isolated bacterial species were subjected to disinfectants and antiseptics impregnated with filter paper discs (disk diffusion assay). The disinfectants and antiseptics used were; Hydrogen peroxide (H2O2), OROLIN® Multisept plus (Orolin), Chlorhexidine (CHX), 84 Disinfectant, ACTOSAL® Flache AF (Actosal) and Ethyl alcohol. Results: In the present study found that the most effective was H2O2 antiseptic against the tested bacterial pathogens with inhibition diameters of 10 to 26mm, except for Proteus bacteria which illustrated resistance at high concentrations. Similarly, Orolin disinfectant shows very excellent efficacy against tested bacteria, and even with low concentrations. Good efficacy was observed for Actosal disinfectant on all species with diameters of inhibition ranging from 10 to 15mm. S. aureus in particular was very sensitive to 70% Ethyl alcohol (20mm), while all tested species were slightly insensitive to both Ethyl alcohol and CHX. In contrast, no effect of the 84 disinfectant was observed on most of isolates. Conclusion: The results of this study indicated that Orolin disinfectant had comparable effects to H2O2 atiseptic but less than to Actosal, 70% Ethyl alcohol and CHX, whereas 84 disinfectant was the weakest one. This study suggests the necessity of applying continuous monitoring to determine the antimicrobial efficacy of these antimicrobial agents regularly. الخلفية والأهداف. تستخدم المطهرات والمعقمات على نطاق واسع في المستشفيات ومراكز الرعاية الصحية لضمان الوقاية من عدوى المستشفيات وتوفير مكافحة العدوى بكفاءة. أظهرت العديد من الدراسات مؤخرًا أن البكتيريا المكتسبة من المستشفيات تطور مقاومة ضد هذه المركبات. الغرض من هذه الدراسة هو فحص مدى فعالية المطهرات والمعقمات الشائعة الاستخدام ضد مجموعة من البكتيريا المعزولة من مستشفى جامعة طرابلس، ليبيا. طرق الدراسة. تم الحصول على خمسة أنواع بكتيرية معزولة من مختلف أقسام المستشفي الجامعي و هيklebsiella spp.، Proteus spp.، E. coli، Acinetobacter spp.،S. aureus . أجريت زراعة هذه الأنواع البكتيرية المعزولة في مولر هينتون أجار (MHA) و تعرضت للمطهرات و المعقمات المشربة بأقراص ورق الترشيح. وكانت المطهرات والمعقمات المستخدمة هي: بيروكسيد الهيدروجين (H2O2)،OROLIN® Multisept plus (الأورولين)، الكلورهيكسيدين (CHX)، مطهر 84،ACTOSAL® Flache AF (أكتوسال) والكحول الإيثيلي. النتائج. في الدراسة الحالية وجد أن المطهر الأكثر فعالية هو H2O2 ضد البكتيريا المعزولة التي تم اختبارها بأقطار تثبيط تراوحت بين 10 إلى 26 ملم، باستثناء بكتيريا Proteus التي أظهرت مقاومة عند التراكيز العالية. وبالمثل، يُظهر مطهر الأورولين فعالية ممتازة جدًا ضد البكتيريا التي تم اختبارها، وحتى مع التركيزات المنخفضة. وقد لوحظت فعالية جيدة لمطهر أكتوسال على جميع الأنواع التي تتراوح أقطار تثبيطها من 10 إلى 15 ملم. كانت S. aureus على وجه الخصوص حساسة جدًا للكحول الإيثيلي (20 مم)، في حين كانت جميع الأنواع التي تم اختبارها قليلة الحساسة لكل من الكحول الإيثيلي و.CHX في المقابل، لم يلاحظ أي تأثير للمطهر 84 على أغلب البكتيريا المعزولة. الخلاصة. أشارت نتائج هذه الدراسة إلى أن مطهر الأورولين كان له تأثيرات مماثلة لمطهر H2O2 ولكن أقل من أكتوسال والكحول الإيثيلي وCHX، في حين كان مطهر 84 هو الأضعف. تشير هذه الدراسة إلى ضرورة تطبيق المراقبة المستمرة لتحديد فعالية مضادات الميكروبات لهذه العوامل المضادة للميكروبات بانتظام.